Applying SWAT model to simulate streamflow in Ben Hai River Basin in response to climate change scenarios - Son, Nguyen Thanh; Nhu, Nguyen Y (VNU Journal of Science: Earth and Environmental Sciences; Vol 25 No 3, 2009)
Abstract